Conversion from forests to pastures in the Colombian Amazon leads to contrasting soil carbon dynamics depending on land management practices. (4th April 2016) - Navarrete, Diego; Sitch, Stephen; Aragão, Luiz E. O. C.; Pedroni, Lucio
Abstract: Strategies to mitigate climate change by reducing deforestation and forest degradation (e.g. REDD+) require country‐ or region‐specific information on temporal changes in forest carbon (C) pools to develop accurate emission factors. The soil C pool is one of the most important C reservoirs, but is rarely included in national forest reference emission levels due to a lack of data. Here, we present the soil organic C (SOC) dynamics along 20 years of forest‐to‐pasture conversion in two subregions with different management practices during pasture establishment in the Colombian Amazon: high‐grazing intensity (HG) and low‐grazing intensity (LG) subregions. We determined the pattern of SOC change resulting from the conversion from forest (C3 plants) to pasture (C4 plants) by analysing total SOC stocks and the natural abundance of the stable isotopes 13 C along two 20‐year chronosequences identified in each subregion. We also analysed soil N stocks and the natural abundance of 15 N during pasture establishment. In general, total SOC stocks at 30 cm depth in the forest were similar for both subregions, with an average of 47.1 ± 1.8 Mg C ha −1 in HG and 48.7 ± 3.1 Mg C ha −1 in LG. However, 20 years after forest‐to‐pasture conversion SOC in HG decreased by 20%, whereas in LG SOC increased by 41%. This net SOC decrease in HG was due to a larger reduction in C3‐derived input and to a comparatively smaller increase in C4‐derived C input. In LG both C3‐ and C4‐derived C input increased along the chronosequence. N stocks were generally similar in both subregions and soil N stock changes during pasture establishment were correlated with SOC changes. These results emphasize the importance of management practices involving low‐grazing intensity in cattle activities to preserve SOC stocks and to reduce C emissions after land‐cover change from forest to pasture in the Colombian Amazon.